Sanctioned to Death? The Impact of Economic Sanctions on Life Expectancy and its Gender Gap - Jerg Gutmann; Florian Neumeier; Matthias Neuenkirch (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We empirically analyze the effect of UN and US economic sanctions on life expectancy and its gender gap in target countries. Our sample covers 98 less developed and newly industrialized countries over the period 1977–2012. We employ a matching approach to account for the endogeneity of sanctions. Our results indicate that an average episode of UN sanctions reduces life expectancy by about 1.2–1.4 years. The corresponding decrease of 0.4–0.5 years under an average episode of US sanctions is significantly smaller. In addition, we find evidence that women are affected more severely by the imposition of sanctions. Sanctions not being “gender-blind” can be interpreted as evidence that they disproportionately affect (the life expectancy of) the more vulnerable members of society. We also detect some effect heterogeneity, as the reduction in life expectancy accumulates over time. Furthermore, countries with a better political environment are less severely affected by economic sanctions.
Keywords: F51; F52; F53; I15; 330; Gender Gap; Human Development; Life Expectancy; Sanctions; United Nations; United States